PRELIMINARY STUDY OF ARCHAEOLOGICAL REMAINS AT KONDHAVALE, TAMHINI AND NIVE, TALUKA MULSHI, DIST. PUNE, MAHARASHTRA - Abhijit Thite (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
An archaeological exploration was carried out in Kondhavale, Tamhini and Nive, Taluka Mulshi, Dist. Pune, in the year December 2020 and December 2021. This route is popularly known as Tamhini pass. From Pune, it leads to Mangaon, Mahad, Raigad and Pali (Dist. Raigad). Kondhavale to Nive patch (32 kms) was explored. This paper reveals about 1. Archaeological remains in the area. 2. Link between already documented places in and around this area.